1994
DOI: 10.1007/bf02365442
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol inhibits asialoglycoprotein receptor synthesis but augments its mRNA expression in a human hepatoma cell line

Abstract: The effect of ethanol on the expression of asialoglycoprotein receptor protein and its mRNA was studied in a human hepatoma cell line, HepG2. The number of asialoglycoprotein receptors on the cell surface was decreased to 60% of the control level, without a loss in affinity, by incubating the cells with 100 mM ethanol. The decrease in cell surface asialoglycoprotein receptors was paralleled by a decrease in total receptor numbers, including intracellular and surface receptors. The internalization of asialoglyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Therefore, we speculated that alternative mechanisms might involve the direct release of one or more humoral factors from ethanol-injured hepatocytes that stimulate collagen synthesis in HSCs and liver fibroblasts. We previously disclosed that human hepatoblastoma HepG2 cells are highly potent in metabolizing ethanol in a similar manner as normal hepatocytes (Kato et al, 1998;Kohgo et al, 1994). We then found that a~6,000 Da polypeptide secreted from ethanolexposed HepG2 cells was capable of stimulating collagen synthesis in human fibroblast IMR-90 cells (Inui et al, 1996).…”
mentioning
confidence: 89%
“…Therefore, we speculated that alternative mechanisms might involve the direct release of one or more humoral factors from ethanol-injured hepatocytes that stimulate collagen synthesis in HSCs and liver fibroblasts. We previously disclosed that human hepatoblastoma HepG2 cells are highly potent in metabolizing ethanol in a similar manner as normal hepatocytes (Kato et al, 1998;Kohgo et al, 1994). We then found that a~6,000 Da polypeptide secreted from ethanolexposed HepG2 cells was capable of stimulating collagen synthesis in human fibroblast IMR-90 cells (Inui et al, 1996).…”
mentioning
confidence: 89%
“…In a previous study, we examined whether HepG2 cells had a metabolic pathway for ethanol as a normal hepatocyte function, and we showed that these cells had significantly high alcohol dehydrogenase (ADH) activity (similar to that in rat liver tissue), and this activity was similar to that in human liver in vivo. 16 In the present study, we incubated the HepG2 cells with 100 mM ethanol; as such a high blood level of ethanol has been found in patients with alcoholic liver disease, 24,25 this concentration seemed to be suitable for an in vitro experiment. This concentration had previously been used in an investigation of the effects of ethanol on human macrophage functions.…”
Section: Discussionmentioning
confidence: 96%
“…6,8 Most of these proteins are glycoproteins, which are catabolized exclusively by AGPRs in hepatic parenchymal cells. 16,20,22 The human hepatoma cell line, HepG2, used in this study shows numerous normal hepatocyte functions, such as the synthesis and secretion of serum glycoproteins, 14 and the ability to internalize and degrade asialoglycoproteins mediated by the AGPRs. 20 We therefore selected the HepG2 cell line as a model for studying the effects of cytokines on the expression of AGPRs in human hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations